The effects of the FIFA 11+ program on lower limb functional outcomes: A systematic review - Yulingga Nanda Hanief; Italo Sannicandro; Raja Mohammed Firhad Raja Azidin (CV Rezki Media, 2025)
Background: The FIFA 11+ program has been proven effective in preventing soccer injuries, but evidence regarding its impact on lower extremity functional outcomes is still scattered and reported heterogeneously. Objectives: This systematic review aims to synthesize evidence regarding the effects of the FIFA 11+ program on lower extremity functional outcomes—including ROM, knee extension, internal and external hip rotation, and hamstring muscle strength—in athletes. Methods: This systematic review was prospectively registered in PROSPERO (CRD420251147261) and conducted in accordance with PRISMA 2020 guidelines. A total of 14 studies involving athletes or physically active individuals met the inclusion criteria. Functional outcomes were measured using various instruments, primarily an isokinetic dynamometer for muscle strength and a goniometer for ROM measurement. The methodological quality of the studies was assessed using the Newcastle–Ottawa Scale. Due to substantial heterogeneity in study design, measurement instruments, intervention protocols, and reporting formats, a quantitative meta-analysis was not performed, and the data were synthesized using a qualitative narrative approach. Results: Most studies (approximately 70–80%) reported an increase in hamstring muscle strength after the FIFA 11+ intervention, particularly in concentric and eccentric isokinetic measurements. Improvements in ROM and functional outcomes of the knee and hip were also reported, although results varied between studies. Evidence related to knee extension and hip rotation shows lower consistency compared to hamstring strength. Conclusions: The FIFA 11+ program shows potential functional benefits beyond injury prevention, particularly in improving hamstring muscle strength and several aspects of joint mobility.